The Membrane Proteins Involved in Virulence of Cronobacter sakazakii Virulent G362 and Attenuated L3101 Isolates - Ye, YingWang; Gao, Jina; Jiao, Rui; Li, Hui; Wu, Qingping; Zhang, Jumei; Zhong, Xian (Frontiers in Microbiology, 2015)
Cronobacter sakazakii is an opportunistic foodborne pathogen and the virulence differences were previously documented. However, information about membranous proteins involved in virulence differences was not available. In this study, virulent characterization such as biofilm formation and flagella motility between virulent C. sakazakii isolate G362 and attenuated L3101 were determined. Then, two-dimensional gel electrophoresis (2-DE) technology was used to preliminarily reveal differential expression of membranous proteins between G362 and L3101. On the mass spectrometry (MS) analysis and MASCOT research results, fourteen proteins with differential expression were successfully identified. At the threshold of 2.0 fold changes, five out of eight membranous proteins were up-regulated in G362. Using RT-PCR, the expression abundance of the protein (enzV, ompX, lptE, pstB, and OsmY) genes at mRNA levels was consistent with the results by 2-DE method. The findings presented here provided novel information and valuable knowledge for revealing pathogenic mechanism of C. sakazakii.